Autonomy, Freedom and Rights - Santoro, Emilio. author. aut Link
X, 294 p.
Keywords: Autonomy, viewed as a subject's autonomous designing of her own distinctive 'individuality', is not a constitutive problem for liberal theory. Since its earliest formulations, liberalism has taken it for granted that protecting rights is a sufficient guarantee for the primacy of individual subjectivity. The most dangerous legacy of the 'hierarchical-dualist' representation of the subject is the primacy given to reason in defining an individual's identity. For Santoro freedom is not a fixed measure. It is not the container of powers and rights defining an individual's role and identity. It is rather the outcome of a process whereby individuals continuously re-define the shape of their individuality. Freedom is everything that each of us manages to be in his or her active and uncertain opposition to external 'pressures'.